Spray drift evaluation with point clouds data of 3D LiDAR as a potential alternative to the sampling method - Li, Longlong; Zhang, Ruirui; Chen, Liping; Liu, Boqin; Zhang, Linhuan; Tang, Qing; Ding, Chenchen; Zhang, Zhen; Hewitt, Andrew J. (Frontiers in Plant Science, 2022)
Spray drift is an inescapable consequence of agricultural plant protection operation, which has always been one of the major concerns in the spray application industry. Spray drift evaluation is essential to provide a basis for the rational selection of spray technique and working surroundings. Nowadays, conventional sampling methods with passive collectors used in drift evaluation are complex, time-consuming, and labor-intensive. This aim of this paper is to present a method to evaluate spray drift based on 3D LiDAR sensor and to test the feasibility of alternatives to passive collectors. Firstly, drift measurement algorithm was established based on point clouds data of 3D LiDAR. Wind tunnel tests included three types of agricultural nozzles, three pressure settings and five wind speed settings were conducted. LiDAR sensor and passive collectors (polyethylene lines) were positioned downwind of nozzle to measure drift droplets in vertical plane. Drift deposition volume on each line and the number of LiDAR droplet points in the corresponding height of the collecting line were calculated, and the influencing factors of this newly method were analyzed. The results show that, 3D LiDAR measurements provide a rich spatial information, such as the height and width of the drift droplet distribution, etc. High coefficients of determination (R2＞0.75) were observed for drift points measured by 3D LiDAR compared to the deposition volume captured by passive collectors, and the anti-drift IDK12002 nozzle at 0.2 MPa spray pressure has the largest R2 value, which is 0.9583. Drift assessment with 3D LiDAR is sensitive to droplet density or drift mass in space and nozzle initial droplet spectrum, in general, larger droplet density or drift mass and smaller droplet size are not conducive to LiDAR detection, while the appropriate threshold range still needs further study. This study demonstrates 3D LiDAR has the potential to be used as an alternative tool for rapid assessment of spray drift.